Resistances and variations of the construction of the gender in the new serial fiction. ’Girls’ and ’Big Little Lies’ - Parra García, Paula; Postigo Gómez, Inmaculada; Vera Balanza, Teresa (Comunicación y Género [Communication and Gender], 2019)
We live in a society in which the differences between what is culturally and socially ascribed to gender survive and persist. This distinction is based on a structure of gender-related stereotypes that affects all areas of our daily lives, including audiovisual media such as gender devices or technologies. Built as everyday discourses, we do not even question what we see on the screen and assume it as representations of our reality. Attending to the incorporation of more and diverse female characters but knowledgeable about the strategies of the audiovisual industry to segment and retain audiences, we propose an analysis of the TV series Girls and Big Little Lies whose objective is to verify which roles women play in serial fictions.